The Symbolic Meaning of a Journey in Joyce's Portrait and Woolf's To The Lighthouse ; British Council Conference on Places and Spaces, 8.- 12.09.2003. Delphi, Greece - Gjurgjan, Ljiljana Ina (2003)
The presentation looks into the ways in which journey functions as a metaphor in Portrait and Lighthouse, intertextually interwoven into the traditional understanding of a journey, in Portrait it symbolizes the ultimate liberalization of an artist. In Lighthouse it stands for the centering and self-realization of the ego in his quest for the existential meaning.
ENG